2021
DOI: 10.1002/deo2.58
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of single‐balloon overtube for endoscopic submucosal dissection in the proximal colon: A propensity score‐matched analysis

Abstract: Objectives A single‐balloon overtube (SBO) can improve poor scope operability during colonic endoscopic submucosal dissection (ESD). We aimed to evaluate the clinical usefulness of SBO for ESD in the proximal colon and the predictive factors for cases in which SBO is useful. Methods A total of 88 tumors located in the proximal colon resected by balloon‐assisted ESD (BA‐ESD) using SBO and 461 tumors resected by conventional ESD (C‐ESD) between June 2015 and November 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…This method was also used for colonic endoscopic submucosal dissection with poor endoscope operability to stabilize the scope position. 26,27 Double-balloon-assisted colonoscopy (DBC) is also used in rescuing patients with incomplete conventional colonoscopy before. Studies had been carried out to compare DBC and SBC in this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was also used for colonic endoscopic submucosal dissection with poor endoscope operability to stabilize the scope position. 26,27 Double-balloon-assisted colonoscopy (DBC) is also used in rescuing patients with incomplete conventional colonoscopy before. Studies had been carried out to compare DBC and SBC in this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can examine colonic mucosa more completely without risk of rapid slipping out of endoscope during withdrawal. This method was also used for colonic endoscopic submucosal dissection with poor endoscope operability to stabilize the scope position 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…BAE may reduce the risk of intraoperative perforation. A propensity score matching analysis comparing BAE-ESD and C-ESD in the proximal colon revealed that BAE-ESD significantly decreased intraoperative perforation for lesions ≥ 40 mm in diameter (0% vs 24%, P = 0.0188), although there were no significant differences in the en bloc resection rate (95% vs 99%, P = 0.17), R0 resection rate (92% vs 96%, P = 0.30), mean dissection speed (16 mm 2 /min vs 16 mm 2 /min, P = 0.53), and intraoperative perforation (5% vs 6%, P = 0.73) between BAE-ESD and C-ESD[ 14 ]. Combining T-ESD with BAE may improve procedure-related outcomes in colorectal ESD cases with poor endoscope maneuverability.…”
Section: Factor Associated With Difficulty In Colorectal Esd: Poor En...mentioning
confidence: 99%
“…The efficacy of balloon-assisted ESD (BA-ESD) as an approach for proximal colorectal tumors has been reported. 1 However, some cases fail to reach the lesion even with balloon-assisted endoscopy (BAE) because of the intestinal loops and excessive intestinal elongation. (Figure 1b), and Kudo's pit pattern classification after crystal violet staining showed types IIIL and IV pit patterns (Figure 1c,d).…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) for proximal colorectal tumors is at times difficult because of the formation of intestinal loops during long procedures, leading to paradoxical movement. The efficacy of balloon‐assisted ESD (BA‐ESD) as an approach for proximal colorectal tumors has been reported 1 . However, some cases fail to reach the lesion even with balloon‐assisted endoscopy (BAE) because of the intestinal loops and excessive intestinal elongation.…”
Section: Introductionmentioning
confidence: 99%